La facultad fiscal de acusación complementaria regulada en el código procesal penal y su posible vulneración al derecho de defensa - Jesús Ventura, Milagros (2012)
The proper administration of justice is an end to all justice system of a given State pursued, which is why using various state policies that often materialize in legislation, it is a solution to all situations that prevent getting this purpose. One of the most latent problems in the field of criminal law is impunity, it understood the lack of punishment for a crime, but combating this problem can not breach the main basis on which sits the Peruvian Criminal Procedure; therefore the analysis of the Indictment Additional Accusation Fiscal Faculty regulated in the Code of Criminal of 2004, instituted procedural figure to avoid cases of impunity, is of great importance to study. This particular research attempts to determine whether the procedural institution violates the right to defense and to determine the requirements for your application, correct interpretation and parameters of that figure. This study is based on doctrinal analysis of the institutions of the Accusation, the Right to Defense and Case Theory, figures that are closely related to the Indictment Complementary, the same that were used to determine the concept, nature, requirements, and Complementary parameters of the Indictment. It also appealed to comparative law analysis of this figure in order to verify its regulation and the relationship they have with our system, and to verify the analysis in this research survey was applied to prosecutors and defense lawyers Judicial District of La Libertad, obtaining highlights data for our research